Keeping identity at a distance: explaining France's new legal restrictions on the Islamic headscarf - Thomas, Elaine R. (Ethnic and racial studies, 2006)
Since 1989, France has endured repeated, contentious debates about the 'Islamic' headscarf. In February 2004, French legislators approved a new law prohibiting students from wearing conspicuous 'religious signs' in public schools. Contrary to some observers' assumptions, this measure was not caused mainly by new efforts to combat terrorism or by pro-Christian prejudice. Explaining France's decision to pass this surprising new legislation requires attention to both historical continuities of French political thinking and the changing French and international context. French republican understandings of citizenship and seclarism have long made the headscarves issue peculiarly sensitive in France. However, the new law marks a clear departure from previous French policy. Explaining that rupture requires attention to more immediate social and political factors, most importantly: dissatisfaction with the previous policy; effective mobilization of public sympathy by new feminist groups; concern about rising anti-Semitism; and, somewhat paradoxically, developments in international human rights law. (Ethnic and Racial Studies)